Applicability of the direct displacement-based design procedure to concentrically braced frames with setbacks. Issue 3 (3rd July 2021) - Salawdeh, Suhaib
ABSTRACT: The objective of this paper is to investigate and develop seismic design guidelines for multi-storey vertical irregular concentrically braced frames (CBFs). The work develops a direct displacement-based design (DDBD) procedure for irregular CBFs associated with steps in building plan area. In this procedure, design displacements considered are decided upon the code and material drift limits, then the strength required to achieve this displacement is calculated and finally all structural elements are designed. A case study of a 12-storey CBF structure with vertical irregularity is designed using the developed DDBD procedure. The configuration of the vertical irregularity assessed is in the form of setbacks up the vertical axis of the building where the frames have more bays at the base of the building than at the top. Non-linear time history analysis (NLTHA) using seven different accelerograms with displacement response spectra matching the design displacement spectrum are used to record the behaviour of the irregular CBF structure when subjected to real earthquakes. It is found that the design displacements and storey drifts from the DDBD procedure for the case study matched relatively well with those recorded through the NLTHA analyses and a new DDBD procedure for CBFs with vertical irregularity is validated.